2020
DOI: 10.1055/s-0040-1713171
|View full text |Cite
|
Sign up to set email alerts
|

Association of Successful Ultrasound-Accelerated Catheter-Directed Thrombolysis with Postthrombotic Syndrome: A Post Hoc Analysis of the CAVA Trial

Abstract: Background The CAVA trial did not show the anticipated risk reduction for postthrombotic syndrome (PTS) after thrombus removal via additional ultrasound-accelerated catheter-directed thrombolysis (UACDT) in patients with acute iliofemoral deep vein thrombosis (IFDVT). Difficulties in achieving an effective degree of recanalization through thrombolysis may have influenced outcomes. We therefore assessed whether successful UACDT (restored patency ≥ 90%) did reduce the development of PTS. Methods This C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…It was shown that pulsed cavitational ultrasound therapy was able to recanalize noninvasively in an in vitro model of acute venous thrombosis 120 . A post hoc analysis of the CAVA (ultrasound‐accelerated catheter‐directed thrombolysis versus anticoagulation for the prevention of post‐thrombotic syndrome) trial of risk for postthrombotic syndrome after early thrombus removal via additional ultrasound‐accelerated, catheter‐directed thrombolysis in patients with acute iliofemoral DVT showed a significant reduction in symptom severity and improvement of generic quality of life 121 . One study of a PE response team investigated the use of catheter‐directed thrombolysis versus systemic intravenous thrombolysis or thrombectomy 122 .…”
Section: International Society On Thrombosis and Haemostasis 2020 Conmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that pulsed cavitational ultrasound therapy was able to recanalize noninvasively in an in vitro model of acute venous thrombosis 120 . A post hoc analysis of the CAVA (ultrasound‐accelerated catheter‐directed thrombolysis versus anticoagulation for the prevention of post‐thrombotic syndrome) trial of risk for postthrombotic syndrome after early thrombus removal via additional ultrasound‐accelerated, catheter‐directed thrombolysis in patients with acute iliofemoral DVT showed a significant reduction in symptom severity and improvement of generic quality of life 121 . One study of a PE response team investigated the use of catheter‐directed thrombolysis versus systemic intravenous thrombolysis or thrombectomy 122 .…”
Section: International Society On Thrombosis and Haemostasis 2020 Conmentioning
confidence: 99%
“…120 A post hoc analysis of the CAVA (ultrasound-accelerated catheter-directed thrombolysis versus anticoagulation for the prevention of post-thrombotic syndrome) trial of risk for postthrombotic syndrome after early thrombus removal via additional ultrasound-accelerated, catheter-directed thrombolysis in patients with acute iliofemoral DVT showed a significant reduction in symptom severity and improvement of generic quality of life. 121 One study of a PE response team investigated the use of catheter-directed thrombolysis versus systemic intravenous thrombolysis or thrombectomy. 122 A study of patients with acute ischemic stroke undergoing thrombolysis showed that low α2-plasmin inhibitor antigen levels on admission is an independent predictor of unfavorable long-term outcomes.…”
Section: International Society On Thrombosis and Haemostasis 2020 Cmentioning
confidence: 99%
“…30 In contrary to these results, CAVA trial showed that there was no significant reduction of PTS following ultrasound-accelerated catheter-directed thrombolysis in patients with acute iliofemoral DVT. 31 The risk of PTS was not significantly different when compared with standard therapy after 1 year of acute iliofemoral DVT. 32 The ATTRACT trial, compared Pharmaco-mechanical thrombolysis plus standard therapy and standard anticoagulant therapy alone in patients with acute DVT at the femoropopliteal segments and proximal iliac segments.…”
Section: Discussionmentioning
confidence: 84%
“…A post hoc analysis of the Catheter Versus Anticoagulation Alone for Acute Primary (Ilio)Femoral DVT (CAVA) trial focused on the effect of ultrasound-accelerated catheter-directed thrombolysis on the development of the postthrombotic syndrome after 1 year of follow-up; although the risk was not reduced after successful thrombolysis for acute iliofemoral DVT, these patients did report an improvement in the quality of life. 91 Finally, observational data suggest that endovascular treatment of postthrombotic syndrome with stent placement might improve mid-and long-term clinical (functional) scores. 92,93 The Aspirin Plus Rivaroxaban Versus Rivaroxaban…”
Section: Anthithromboti C S Tr Ateg Ie S B E Yond Anti Coag Ul Ati On: Fo Cus On Percutaneous C Athe Ter-d Irec Ted Techni Q U E Smentioning
confidence: 99%